Reconsideration of the native range of the Chinese Swamp Cypress (Glyptostrobus pensilis) based on new insights from historic, remnant and planted populations - Jinlong Zhang (Elsevier, 2021)
Many species in the lowland forest of the Indo-Chinese tropical and subtropical region have lost a substantial amount of suitable habitat due to both historical and contemporary anthropogenic activities. Therefore, conservation programmes that aim to restore or re-establish populations need to consider the species’ recent past range as well as its current, often remnant range.In this study, we modelled the potential distribution of the Chinese Swamp Cypress (Glyptostrobus pensilis), a critically endangered conifer species endemic to East and Southeast Asia using Maxent. We used four types of occurrence records: (1)“buried ancient trees”, (2)“natural”, (3)“planted” and (4)“unknown”. We also tested if the niche differed across different types of records.Our results show that the suitability varied with the type of occurrence records. In particular, the model based on “natural” populations predicted that the species prefers more remote and inland areas, whereas the model based on “planted” records predicted that the species tend to occur in lowland or coastal areas. The suitable ranges based on four different types of records shared a more or less similar pattern but were all broader than the native range previously anticipated. The suitability predicted using the “natural” populations alone may underestimate the species’ ecological amplitude. Incorporating buried ancient trees and outdoor planting locations within or close to the potential native range will help to better understand the species’ ecological niche and suitability. We argue that the Chinese Swamp Cypress’ native range should be reconsidered and potentially has to include the subtropical areas of China and montane areas in Indo-China. Any population growing in relatively natural habitats in this region deserves conservation consideration, given that significantly distinct genetic patterns were found throughout the area. Conservation actions must be taken to secure the persistence of the remaining populations of this critically endangered species.